MANAJEMEN SUMBER DAYA INSANI DI BMT UGT SIDOGIRI - Nuntufa; Mutamakkim Billah (Faculty of Islamic Economics and Business, 2020)
ABSTRACT Introduction : Human resources in BMT UGT Sidogiri in Indonesia have an important role in the development of a company and demonstrate its service capabilities, as evidenced by the large number of customers who raise funds to BMT. The way to find human resources in BMT is by way of recruitment. Recruitment is an important aspect in finding human resources so that they can provide maximum service and performance. This study aims to determine the Human Resource Management at BMT UGT Sidogiri Kraksaan Branch. Methods : This type of research is field research, which in essence is a method to find specifically and realistically what is happening at some point in the community. Meanwhile, the data analysis technique uses qualitative descriptive analysis techniques. Results : The results of this study are as follows: First, the recruitment system at BMT UGT Sidogiri Kraksaan Branch is very good using two methods, namely internal and external recruitment. In addition, there are special considerations in the recruitment system, where these considerations are prioritized for prospective employees from the Sidogiri Islamic Boarding School Alumni who are not required to be graduates of sharia banking and sharia economics. Because the most important thing in being an employee of BMT UGT Sidogiri Kraksaan Branch is an inner bond so that it will create employees who have high loyalty to the organization. Therefore, from the use of these methods and special considerations, BMT can find human resources who have high loyalty and capabilities that can be developed. Second, while in the process of fulfilling the professional demands of BMT UGT Sidogiri Kraksaan Branch using a strategy by means of training and evaluation. Where the training is carried out at the end of the year which is carried out for 5 days and the evaluation is carried out every day for employees and every month for the head of BMT. Keywords: Management, Human Resources, Recruitment, Performance